2020
DOI: 10.3390/cancers12030568
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Glioblastoma Subclinical Recurrence Using Serial Diffusion Tensor Imaging

Abstract: Glioblastoma is an aggressive brain tumor with a propensity for intracranial recurrence. We hypothesized that tumors can be visualized with diffusion tensor imaging (DTI) before they are detected on anatomical magnetic resonance (MR) images. We retrospectively analyzed serial MR images from 30 patients, including the DTI and T1-weighted images at recurrence, at 2 months and 4 months before recurrence, and at 1 month after radiation therapy. The diffusion maps and T1 images were deformably registered longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Radiomics‐based quantitative phenotyping using multivariate classification is prevalent in neuro‐oncology research; however, it has been limited to delineating tumor grade and genotype 35 . Recurrence predictions have been performed on a preoperative scan with a predefined region of interest around the tumor, not accounting for the time duration between the first scan and recurrence, as well as recurrence patterns that may occur at a distant location 14,15,17 . We employ a multivariate classification scheme and create two separate classifiers for distant and local recurrences based on the disparity in the underlying discriminative radiomic patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics‐based quantitative phenotyping using multivariate classification is prevalent in neuro‐oncology research; however, it has been limited to delineating tumor grade and genotype 35 . Recurrence predictions have been performed on a preoperative scan with a predefined region of interest around the tumor, not accounting for the time duration between the first scan and recurrence, as well as recurrence patterns that may occur at a distant location 14,15,17 . We employ a multivariate classification scheme and create two separate classifiers for distant and local recurrences based on the disparity in the underlying discriminative radiomic patterns.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, subtle changes in apparent diffusion coefficient (ADC) and FLAIR quantifiers in the preoperative MRI scan, in the area of relapse, have been illustrated 14 . Recently, multimodal radiomics and diffusion multicompartment models have been employed to predict the recurrence infiltration patterns on preoperative multimodal MRI 14–17 . Nonetheless, these works usually only focus on the pre‐existing peritumoral edema as the area of probable recurrence, while relapse in distant/multifocal locations is not considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, glioma cells are found outside this core region due to the tumoral spread. As glioma cells migrate, it is thought to cause a loss of axonal integrity, leading to increased diffusivity and the T2 signal, and it is difficult to differentiate from vasogenic edema [34,35]. It has been suggested that diffusion imaging can improve the identification of non-enhancing tumour infiltration.…”
Section: Dti Modelled Tumoral Invasionmentioning
confidence: 99%
“…Despite the introduction of tumor-treating fields and the vascular epithelial growth factor (VEGF) inhibitor bevacizumab [ 4 , 5 ] to the standard approach of radical resection followed by concomitant radiochemotherapy [ 6 , 7 ] and significant advancements regarding guided surgical resection including the application of 5-aminolevulinic acid and contrast-enhanced ultrasound [ 8 ], this glioma subtype still marks a therapeutical challenge [ 9 , 10 , 11 , 12 , 13 ] and has the poorest prognosis with a median survival of under two years [ 14 ]. Furthermore, its high recurrence rate [ 15 ] limiting the patient’s survival represents a radiologic problem: Innumerable studies tried to differentiate between recurrent tumors and treatment related changes [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]—a question with the highest clinical impact [ 25 , 26 ] and a neuroradiological challenge. Whereas initial diagnosis of GBM is often reliably feasible due to its typical radiological features, e.g., peripheral irregular ring enhancement, intralesional hemorrhage, and central necrosis [ 7 , 27 , 28 ], imaging of recurrent and/or progressive residual high-grade GBM is similar to therapy associated cerebral radiation necrosis (increasing contrast enhancement and progressive peritumoral edema at least six months up to several years after radiotherapy [ 29 ], often progresses without treatment) or pseudoprogression (increasing contrast enhancement and progressive peritumoral edema within three to six months following radiotherapy, often resolves spontaneously) after surgical resection and concomitant radiochemotherapy; both show strong contrast enhancement, increasing fluid-attenuated inversion recovery (FLAIR) hyperintensities adjacent to the enhancement, and present with punctiform intralesional hemorrhage and necrosis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%